2021
DOI: 10.3390/antiox10081295
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Effects of Bischofia javanica (Blume) Leaf Methanol Extracts through the Regulation of Nrf2 and TAK1

Abstract: Bischofia javanica (Blume) has been traditionally used to treat inflammatory diseases such as tonsillitis and ulcers throughout Asia, including China, Indonesia, and the Philippines: however, the molecular mechanisms by which B. javanica exerts its antioxidant and anti-inflammatory properties remain largely unknown. In this study, we analyzed the antioxidant and anti-inflammatory mechanisms of methanol extracts of B. javanica leaves (MBJ) in vitro and in vivo. MBJ decreased nitric oxide (NO) production and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Geographically, Pepolo is native to South Asia, Southeast Asia, Australia, and China, and it is widely distributed across Western India, Southern Japan, Eastern Australia, the Pacific, O n l i n e F i r s t and the Indonesian Archipelago (Kundu et al, 2020). Several studies have demonstrated the pharmacological action of Pepolo as an anti-inflammatory (leaves), antioxidant (bark and leaves), antileukemic (leaves), antimicrobial, antiallergic, antitussive (leaves), anthelmintic (leaves), antidiarrheal (stem bark), antidiabetic, antinematode, and antimicrobial agent and as a hair growth stimulant (stem and leaf bark) an antiaging agent for the skin and for treating burns (bark) (Kundu et al, 2012;Lee et al, 2021;Lingadurai et al, 2011;Rajbongshi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Geographically, Pepolo is native to South Asia, Southeast Asia, Australia, and China, and it is widely distributed across Western India, Southern Japan, Eastern Australia, the Pacific, O n l i n e F i r s t and the Indonesian Archipelago (Kundu et al, 2020). Several studies have demonstrated the pharmacological action of Pepolo as an anti-inflammatory (leaves), antioxidant (bark and leaves), antileukemic (leaves), antimicrobial, antiallergic, antitussive (leaves), anthelmintic (leaves), antidiarrheal (stem bark), antidiabetic, antinematode, and antimicrobial agent and as a hair growth stimulant (stem and leaf bark) an antiaging agent for the skin and for treating burns (bark) (Kundu et al, 2012;Lee et al, 2021;Lingadurai et al, 2011;Rajbongshi et al 2014).…”
Section: Introductionmentioning
confidence: 99%